Incidencia de la adecuada ejecución financiera y presupuestal de los fondos públicos rubros 08 (Impuestos Municipales) y 09 (Recursos Directamente Recaudados) en el resultado de la Gestión Municipal de la provincia de Chepén durante el año fiscal 2014. - Suárez Cabanillas, Jhonny Luis (2016)
This research was conducted with the aim of contribute to the organic, functional and operational improvement of the Unit of Management and Budget of the Provincial Municipality of Chepen, through an integrative proposal as a result of a thorough investigation, which has allowed measure the financial impact that hauled the performing of actions and procedures performed in the Finance and Budget Execution of own resources of the Provincial Municipality of Chepen. In the development of this work all the activities carried out within the Provincial Municipality of Chepen regarding how and prioritization of Expenditure Revenue collected directly. Measured and evaluated using descriptive method that had to collect basic information in order to be classified, analyzed and compared to the current regulations and accounting instructions have enabled their timely and actual valuation, which consequently have been expressed by administrative acts through Document Management Regulations based on prevailing in the framework of actions of public administration, providing a high degree of reliability of the processed information. It is necessary that local governments through their mayors concern actions and affirm resources to implement policies and management of human and financial resources for a better monitoring of accounting and administrative policies of the assets of the Municipality, for which the equipment must be purchased with their respective installed software because without it the execution of all actions to carry out would be limited.